Probing the depths of evil and good : multireligious views and case studies - Gort, Jerald D.; Jansen, Henry; Vroom, H. M., 1945-2014 (Rodopi, 2007)
In the few years since the attack on the World Trade Center on September 11, 2001, evil has become a central theme in the media and human consciousness: the evil of terrorism, the evil of secular culture, concern for poverty, and climate change ... Yet different cultures and religious traditions have different ideas of what evil is and what its root causes are. Although there is no massive clash of cultures, many disagreements and also conflicts in the world arise from the deep differences in views of evil. This volume explores religious views of evil. Scholars from different religions and fr.
Keywords: Ethics.; Good and evil -- Religious aspects.; Ethics; Morale.; ethics (philosophy); PHILOSOPHY -- Social.; PHILOSOPHY -- Ethics & Moral Philosophy.; Good and evil -- Religious aspects; Das Gute; Das Böse; Religion; Het Kwaad.; Godsdiensten.